Household costs, catastrophic out-of-pocket payments and impoverishment related to accessing surgical care in rural Ethiopia - Yohannes Hailemichael; Tigist Eshetu; Sewit Timothewos; Andualem Deneke; Amezene Tadesse; Ahmed Abdella; Abebe Bekele; Andrew Leather; Girmay Medhin; Martin Prince; Charlotte Hanlon (PLoS ONE, 2026)
Background The objective of this study was to assess the household costs, catastrophic out-of-pocket (OOP) health expenditure, impoverishment and coping mechanisms used to pay for surgical care in a predominantly rural area of Ethiopia. Methods We conducted a community-based, cross-sectional household survey of 182 people who had undergone a surgical procedure. Participants were interviewed in their homes at six weeks post-operation. Using a contextually adapted version of the Study of global AGEing and adult health (SAGE) questionnaire, we estimated direct and indirect costs of surgical care from a household perspective. Catastrophic out-of-pocket (OOP) health expenditure was estimated using thresholds of 10% and 25% of annual household consumption expenditure. Impacts of surgical care payments on poverty levels was estimated by comparing pre- and post-operative OOP payments. Analysis of variance, t-test and a logit model were used to assess factors associated with catastrophic OOP health expenditure. Results Most surgical patients were women (87.9%), with 65.0% receiving obstetric surgical care. Direct costs dominated expenditure: direct average medical costs Birr 1649.5 (44.6%), direct average non-medical costs Birr 1226.5 (33.2%), indirect average costs Birr 821.9 (22.2%). Catastrophic OOP surgical care expenditure was experienced by 69.2% households at the 10% threshold and 45.6% at the 25% threshold. The increase in average normalized poverty gap due to OOP surgical care expenditure was higher in non-obstetric (14.1%) compared to obstetric (5.8%) procedures, and for non-emergency (13.3%) compared to emergency care (6.3%). To pay for surgical care, 38.0% of households had sold assets and 5.0% had borrowed money. Conclusions Due to surgical care, households faced severe financial burdens leading to impoverishment. To mitigate the resulting financial constraints, households implemented hardship coping strategies. Provision of free obstetric surgical care reduced, but did not eliminate, these burdens. There is a pressing need to tailor financial risk protection mechanisms to achieve universal coverage for surgical care.